Unsymmetrical Difunctionalization of Two Different C–H Bonds in One Pot Under Transition-Metal Catalysis - Murai, Masahito; Takai, Kazuhiko (Synthesis, 2019)
Recent advancements in unsymmetrical difunctionalization based on the substitution of two different C–H bonds in one-pot are described. Due to the difficulty of controlling reactivity and selectivity, multi-functionalization via substitution of several C–H bonds to install different functional groups has been limited until recently, in comparison with well-studied functionalization via sequential addition to unsaturated π-bonds. This difunctionalization protocol provides an efficient and rapid approach to a library of structurally complicated target molecules through the formation of multiple C–X bonds with high atom- and step-economy.1 Introduction2 ortho-Selective Functionalization of Two Different C–H Bonds Relative to the Directing Group2.1 Unsymmetrical Difunctionalization with the Introduction of Similar Functional Groups2.2 Unsymmetrical Difunctionalization with the Introduction of Different Functional Groups2.3 ortho-Selective Unsymmetrical Difunctionalization Promoted by Two Different Directing Groups Appearing During the Progress of the Reaction3 ortho/meta-Selective C–H Bond Difunctionalization Relative to the Directing Group4 Sequential Difunctionalization of Fused Aromatic Compounds and Heterocycles5 Summary and Outlook
Keywords: difunctionalization; C–H activation; regioselectivity